2017
DOI: 10.1002/hsr2.14
|View full text |Cite
|
Sign up to set email alerts
|

Increased energy expenditure during posture maintenance and exercise in early Parkinson disease

Abstract: Background: Evidence for the effects of Parkinson disease on energy expenditure is incom-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In addition, accurate assessments of abnormal muscle tone and involuntary movements caused by cerebrovascular and neurodegenerative diseases will lead to appropriate nutritional management. It has been reported that oxygen consumption during exercise is higher in patients with Parkinson’s disease than in healthy people (50) , and deep stimulation of the subthalamic nucleus increases body weight and BMI (51) . In addition, it has been reported that energy expenditure is higher in patients with cerebellar ataxia than in healthy people because of decreased coordination during walking (52) .…”
Section: The Effect Of Physical Therapy On Nutritionmentioning
confidence: 99%
“…In addition, accurate assessments of abnormal muscle tone and involuntary movements caused by cerebrovascular and neurodegenerative diseases will lead to appropriate nutritional management. It has been reported that oxygen consumption during exercise is higher in patients with Parkinson’s disease than in healthy people (50) , and deep stimulation of the subthalamic nucleus increases body weight and BMI (51) . In addition, it has been reported that energy expenditure is higher in patients with cerebellar ataxia than in healthy people because of decreased coordination during walking (52) .…”
Section: The Effect Of Physical Therapy On Nutritionmentioning
confidence: 99%